Automatic Bird Feeder Prototype Design Using Esp8266 Microcontroller Based On Android - aji nurrohman; Berliyanto; Sigit Wibisono; Surya Darma; Wibisono; Leni Devera Asrar; Triyono Budi Santoso (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
To make life easier for pet owners, a product titled "Prototype Design of Automatic Bird Feeding Tool with Android-Based NodeMcu EPS8266 Microcontroller" was created. When a pet owner is unable to control his pet's diet, a tool that is connected to the internet is required to make it simpler for the pet owner to monitor remotely using an Android device. The system device is made up of numerous components, including a NodeMcu ESP8266 microcontroller, a servo motor for opening and closing a feed door, and an RCT DS3231 digital timer for output. A Blynk application connected to the gadget is installed on the pet owner's smartphone and allows for remote monitoring.